African-American Music in the Service of White Nationalists: Polish “Patriotic Rap” as a Pop Cultural Tool to Promote National Values - Piotr Majewski (European Journal of American Studies)
In today’s world, cultural products, technologies, information and ideologies easily transcend national borders, and the history of the internationalization of rap music is a good example of this phenomenon. Rap has not only become a symbol of the IT revolution and the prevalence of the western capitalist business practices, but also a cultural tool used by some marginalized groups to express their identity. The first part of this article explains how rap, having become an important element of African-American culture, enabled its audience and artists to manifest and communicate their ideas, beliefs and values, including those that are rooted in the culture of black nationalism. In the second part, I provide an outline of the history of Polish rap and trace the African-American influences, to finally focus on the rise of a specific Polish subgenre called “patriotic rap.”